Answer:
Step-by-step explanation:
<u>The options:</u>
A. The bases are parallel and congruent.
- Incorrect. There are no parallel bases in any pyramid
B. The segment from the top to the center of the base is perpendicular to the base.
- Correct as its a right pyramid
C. All the faces are congruent pentagons.
- Incorrect. Only the base is pentagon.
D. The base is a pentagon and the sides are triangles.
E. The base must be a regular polygon.
- Incorrect. It is pentagon.
Answer:
1303.45 cm
Step-by-step explanation:
The triangles formed by a rod and its shadow and a tree and its shadow are similar triangles, so the ratios of their heights to the lengths of their shadows are equal.
Let x be the height of the tree. Setting the ratios equal, we get:
180/116 = x/840
Solve for x:
x = 840 * (180/116)
x ≈ 1303.45 cm
Answer:
36.12
Step-by-step explanation:
43% of 84 can be rewritten to 43% * 84 or 43/100 * 84.
43/100 * 84/1 = 3612/100
3612/100 = 36.12
Answer:
Slope intercept: y = -3/2x + 1
Point slope: y + 2 = -3/2 * (x - 2) [Forgot to add the work for this, I will add it if you need it, feel free to ask.]
Step-by-step explanation:
m = (change in y)/change in x)
But also
m = y_2 - y_1/x_2 - x_1
So lets substitute
m = 1 - (-2)/0 - (2)
Lets find the slope
m = 3/0 - (2)
m = 3/-2
m = -3/2 (Moved the negative)
Now we find the value of b using the equation of a line.
y = mx + b
y = (-3/2) * x + b
y = (-3/2) * (2) + b
-2 = (-3/2) * (2) + b
Now we find the value of b
Lets rewrite
-3/2 * 2 + b = -2
Cancel the CF of 2
-3 + b = -2
Move the terms without b to the right
b = -2 + 3
b = 1
Now we substitute our values of the slope and y-int into y = mx + b to find the equation.
y = -3/2x + 1
Here you have to find which each variable is, for this you start of picking one equation,
x + 2y + 6z = 4
-3x + 2y - 2 = -4
4x + 2z = 16
depending the equation you pick you multiply that by a certain number that will give you the opposite of one of the other equations,
-1(x + 2y + 6z = 4)
= -x -2y - 6z = -4
With this you add or subtract it with the equation that has the same number or variable, or both,
In this case it will be the equation,
-3x + 2y + 6z = 4
You can use this one or the third equation since both have a positive 2y which will cancel with -2y from the new equation,
-x - 2y - 6z = -4
-3x + 2y -z = -4
= -4x -7z = -8
Now you since you just eliminated the variable (y) you now have 2 variables, and the last equation has only 2 variables, meaning now you find the answer to those to equations,
-4x -7z = -8
4x + 2z = 16
= -5z = 8
Now leave the variable by itself,
z = 8/5
Now you found the variable (z), with this just substitute on one of the equations we used to find (z) so you can find (x), after that substitute those answered to on of the original equations so you can find (y)